2020
DOI: 10.1139/cjps-2019-0014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the bioregulators ACC, 6-BA, ABA, and NAA as thinning agents on Gala apples

Abstract: Gala apple (Malus domestica Borkh.) trees are prone to heavy cropping but respond to chemical fruitlet thinners to reduce crop load and improve fruit quality. Environmental concerns over the fate of the chemical fruitlet thinner carbaryl is widely acknowledged, but crop load management options are limited. In southern Ontario, Gala trees were treated with new thinning compounds or combinations to determine post-bloom thinning efficacy and resulting fruit quality. Treatments included 6-benzyladenine (6-BA) comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…( Dennis (2003) and Cortens and Cline (2019) shown that fruit thinning improves flower initiation and hence return bloom for the following season. This concurs with our results which showed that the high thinning efficiency can improve the return bloom.…”
Section: Discussionmentioning
confidence: 99%
“…( Dennis (2003) and Cortens and Cline (2019) shown that fruit thinning improves flower initiation and hence return bloom for the following season. This concurs with our results which showed that the high thinning efficiency can improve the return bloom.…”
Section: Discussionmentioning
confidence: 99%
“…6-BA is a synthetic cytokine that can keep plants fresh by delaying the degradation and senescence of protein, nucleic acid, and chlorophyll. It can promote seed germination and seedling growth, thus being widely used in agriculture, horticulture, and other fields [38][39][40]. However, 6-BA is harmful to the human body.…”
Section: Detection Of Pesticide Residuesmentioning
confidence: 99%
“…Many of these products do not require supplemental use of carbaryl for sufficient thinning activity. Abscisic acid is mild thinner that is most effective in combination with other products (Cortens and Cline 2019). Metamitron is a photosynthetic inhibitor with thinning activity when applied at $10 to 20 mm (Basak 2011;McArtney and Obermiller 2012).…”
mentioning
confidence: 99%